2010
DOI: 10.2174/157488910789753503
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Oligonucleotides as an Innovative Therapeutic Strategy in the Treatment of High-Grade Gliomas

Abstract: Despite the intensive recent research in cancer therapy, the prognosis in patients affected by high-grade gliomas is still very unfavorable. The efficacy of classical anti-cancer strategies is seriously limited by lack of specific therapies against malignant cells. The extracellular matrix plays a pivotal role in processes such as differentiation, apoptosis, and migration in both the normal and the pathologic nervous system. Glial tumors seem to be able to create a favorable environment for the invasion of gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 0 publications
0
30
0
1
Order By: Relevance
“…Antisense oligonucleotides are synthetic single strand stretches of oligonucleotides that bind to complementary mRNA and prevent translation. 12 The authors had previously established that P2X3 ASO were effective in reducing P2X 3 mRNA levels and lowering mechanical hyperalgesia but found in the current study that an equivalent dose of siRNA gave a stronger effect. 13 …”
Section: Direct Sirna Deliverymentioning
confidence: 49%
“…Antisense oligonucleotides are synthetic single strand stretches of oligonucleotides that bind to complementary mRNA and prevent translation. 12 The authors had previously established that P2X3 ASO were effective in reducing P2X 3 mRNA levels and lowering mechanical hyperalgesia but found in the current study that an equivalent dose of siRNA gave a stronger effect. 13 …”
Section: Direct Sirna Deliverymentioning
confidence: 49%
“…Obviously the complexity and the cross-talk between signal transduction pathways limit the potential efficacy of targeting a single receptor. On the basis of our results, we demonstrate the role of interleukin-8 (IL-8) as an important angiogenesis mediator within hypoxia inducible factor (HIF-1 ) pathway and crosstalk between hypoxia-induced high levels of HIF-1 and VEGF expression [32][33][34]. An antisense strategy characterized by a simultaneous selective strategy against these two molecular targets involved at different levels of the same pathological pathway could be an attractive therapeutic mechanism aimed at enhancing an anti-angiogenic and antitumoral effect.…”
Section: Current and Future Developmentsmentioning
confidence: 74%
“…In this molecular cascade HIF-1 up-regulated levels finally induce up-regulation of VEGF expression, and, at the same time, may stimulate gene expression of other genes involved in gliomagenesis. Our study group has recently showed high expression levels of PGES-1 (Prostaglandine E 1 Sinthase) and IL-8 in high grade glioma cells and microglial cells, strongly correlated with grading tumor (Caruso et al, 2010a). During malignancy progression gliomagenesis, leukocyte infiltration and necrosis are two biological phenomena associated with the development of neovascularization.…”
Section: Discussionmentioning
confidence: 90%
“…Several experimental in vitro and in vivo studies in cell lines cultures and animal models showed inhibition of genes involved in cell proliferation, apoptosis and angiogenesis. Clinical trials demonstrated a good tolerability and no increment of toxicity of antisense oligonucleotides (Caruso et al, 2010a). However, considering the multitude of molecular entities and signalling pathways that regulate the proliferation and cellular survival/cell death, inhibition of a singular target gene or transcriptional factor could not be sufficient to suppress neoplastic progression.…”
Section: Discussionmentioning
confidence: 99%